LIETUVOS VALSTYBĖS VADOVO INSTITUTAS 1990–1992 m. - Sinkevičius, Vytautas (Teisė, 2015)
Seime įregistruotas įstatymo „Dėl Lietuvos Respublikos Aukščiausiosios Tarybos – Atkuriamojo Seimo Pirmininko teisinio statuso“ projektas1, kuriame konstatuojama, kad 1990–1992 m. dirbusios Aukščiausiosios Tarybos – Atkuriamojo Seimo Pirmininkas yra valstybės vadovas. Seimo nariai projektą vertina nevienodai: vieni teigia, kad toks įstatymas yra būtinas, kiti tvirtina, kad jis prieštarauja Konstitucijai ir Lietuvos Respublikos Konstitucinio Teismo (toliau Konstitucinio Teismo) 2002 m. birželio 19 d. nutarimui. Aukščiausiosios Tarybos – Atkuriamojo Seimo Pirmininko teisinis statusas mokslinėje literatūroje mažai nagrinėtas2. Aukščiausiosios Tarybos – Atkuriamojo Seimo Pirmininko teisinio statuso analizė ir jo įprasminimas įstatymu yra būtinas, siekiant užtikrinti teisinį aiškumą ir tikrumą bei įtvirtinti atkurtos nepriklausomos Lietuvos valstybės vadovo institucijos istorinį ir teisinį tęstinumą nuo to laiko, kai po Lietuvos nepriklausomybės atkūrimo 1918 m. vasario 16 d. buvo išrinktas pirmasis Lietuvos Respublikos Prezidentas. A draft Law “On the Legal Status of the Chairman of the Supreme Council-Reconstituent Seimas” has been registered at the Seimas, in which it is stated that the Chairman of the 1990–1992 Supreme Council-Reconstituent Seimas was the Head of State. The members of the Seimas are somewhat ambivalent about the draft law: some of them assert that such a law is necessary, whereas some others maintain that this law is in conflict with the Constitution and the Constitutional Court’s ruling of 19 June 2002. According to the Provisional Basic Law (Provisional Constitution), the Chairman of the 1990–1992 Supreme Council of the Republic of Lithuania was the highest official of the Republic of Lithuania with the powers to represent the Republic of Lithuania in international relations, to sign laws of the Republic of Lithuania and other acts passed by the Supreme Council, hold talks and sign international treaties of Lithuania, and submit them for ratification to the Supreme Council. He also had the powers to recommend candidates for the appointment or election to the posts of the Prime Minister of the Republic of Lithuania, the President of the Supreme Court of Lithuania, chairmen of divisions of this court, the Prosecutor General of the Republic of Lithuania, etc. The Provisional Basic Law (Provisional Constitution) does not contain the words “the Chairman of the Supreme Council of the Republic of Lithuania shall be Head of State”, however, it does not mean that the independent State of Lithuania restored on 11 March 1990, purportedly, did not have any institution of its Head of State, and that the Chairman of the Supreme Council of the Republic of Lithuania, purportedly, was not Head of State. The fact that the Chairman of the Supreme Council was Head of State is confirmed by the provision “[t]he Chairman of the Supreme Council of the Republic of Lithuania shall be the highest official of the Republic of Lithuania” of the Provisional Basic Law and by the powers provided for the Chairman of the Supreme Council. The compliance of the provisions of the draft Law “On the Legal Status of the Chairman of the Supreme Council-Reconstituent Seimas” with the Constitution of 1992 that is valid at present cannot be questioned on the grounds that, purportedly, this draft law is not in line with both the Provisional Basic Law of 1990 and such a concept of its provisions that were presented by the Constitutional Court in its ruling of 19 June 2002. This draft law should only be viewed through the prism of the Constitution of 1992 that is valid at present.